Family-school relationship expectations - Francisco Tondin, Celso; David Evaristo Panizzi, Alan (Revista Pesquisas e Práticas Psicossociais, 2017)
This article discusses the psychosocial processes in the accomplishment of the family-school integration pedagogical goal, aiming at identifying and analyzing the integrating expectations between professionals and family members of a school community. It is a qualitative research based on the methodology of ethnographic case studies, developed in a public school in Minas Gerais (Brazil), using the participant observation – recorded in field diary – and semi-structured interviews with 21 professionals and 16 relatives, as well as reported files. It was verified that the relatives show pedagogical expectations about support and attention provided by the school to the children, as well as with institutional relationship with families. Professionals, in turn, talk about the responsibility of families in the education of their children and their participation in school every day. The importance of the school as an environment of citizenship and participatory democracy is evidenced. Keywords: Family-school relationship. Family. School. Education. Psychosocial processes.